Implementasi Buku Talaqqi Karya Dr. Surul Shahbudin dalam Memperbaiki Makharijul Huruf Peserta Didik Dewasa - Imelda Wahyuni; Indah Muliati (Lembaga Yasin AlSys, 2026)
Although the teaching of tajwid and makharijul huruf has been widely discussed in previous studies, research on the implementation of Surul Shahbudin’s Talaqqi book in improving makharijul huruf among adult learners remains limited. This study aims to examine the implementation of the use of the Talaqqi book in improving the makharijul huruf of adult learners at Rumah Qur’an Al-‘Amilin Padang. This study employed a qualitative approach with a case study design. The research informants consisted of the institution owner, tahsin teachers, an administrator, and adult learners selected through purposive sampling. Data were collected through observation, interviews, and documentation and were then analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results showed that the Talaqqi book supports systematic and structured learning through the gradual presentation of material, beginning with the introduction of single letters bearing a fathah vowel mark and progressing to letters with tanwin and sukun. The application of the talaqqi method enables direct interaction between teachers and learners so that pronunciation errors can be immediately identified and corrected. Evaluation through direct observation and periodic tests showed an improvement in the ability of adult learners to pronounce hijaiyah letters. These findings contribute to the development of Qur’anic tahsin learning, particularly in the use of structured teaching materials to improve makharijul huruf among adult learners. The conclusion of this study affirms the importance of integrating the talaqqi method and systematic teaching materials in improving the quality of Qur’anic learning. This study also opens opportunities for further research on the effectiveness of using the Talaqqi book across different age groups and learning contexts.